1999
DOI: 10.1063/1.479740
|View full text |Cite
|
Sign up to set email alerts
|

Electron trapping and hydrogen atoms in oxide glasses

Abstract: Absence of recombination of neighboring H atoms in highly purified solid parahydrogen: Electron spin resonance, electron-nuclear double resonance, and electron spin echo studies Transient nucleation in oxide glasses: The effect of interface dynamics and subcritical cluster population Trapped hydrogen atoms generated in 3 MeV ␤-radiolysis of B 2 O 3 :OH glass below 140 K were studied using electron paramagnetic resonance ͑EPR͒. Two types of trapped H atoms were present in this glass; one was an interstitial ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 71 publications
(108 reference statements)
2
13
0
Order By: Relevance
“…Thus, the observed voltammetric results can be understood by a scenario in which an external electric field causes protons to migrate in the oxide layer 24 and the protons are electrochemically reduced to produce H atoms 9,32 in a negative potential regime. Shkrob et al 10 suggested that electrons react with network-bound protons at 180-530 K to produce H atoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the observed voltammetric results can be understood by a scenario in which an external electric field causes protons to migrate in the oxide layer 24 and the protons are electrochemically reduced to produce H atoms 9,32 in a negative potential regime. Shkrob et al 10 suggested that electrons react with network-bound protons at 180-530 K to produce H atoms.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal SiO 2 is a dielectric material used for conventional metal/insulator/metal capacitors 6 , and SiO 2 films are widely used as gate insulators of metal/oxide/semiconductor (MOS) devices 7 , in which the field-induced drift of protons to the Si/SiO 2 interface and their interactions with electrons can create hydrogen (H) atoms at the interface 8,9 . Shkrob et al 10 demonstrated that protons were reduced to generate mobile H atoms in B 2 O 3 glasses at room temperature. Energy calculations revealed that H atoms in SiO 2 are isolated by themselves without a strong interaction with oxygen (O 2 ) or Si atoms.…”
mentioning
confidence: 99%
“…There is no clear distinction between different variants of the hole centers in alkali borate glasses. The observed difference in the spin parameters is due to variations of the immediate environment of the BO 3 -unit. The dangling bond center is an electron trapped on over coordinated oxygen (the "O 3 + " defect).…”
Section: Alkali Borate Glasses (Paper 1)mentioning
confidence: 96%
“…All variants of oxygen hole centers are holes trapped on the nonbridging oxygen in a BO 3 -unit. Alkali cations and protons are excluded from this center; the hole is trapped on under coordinated oxygen (the "O 1 -" defect).…”
Section: Alkali Borate Glasses (Paper 1)mentioning
confidence: 99%
See 1 more Smart Citation